THE EFFECTIVENESS OF THE ICE BREAKING METHOD ON MOTIVATION TO LEARN GRAMMAR - Sherly Yustuti; Masrun Masrun; Agustiar Agustiar; Fathah Rizki Mubina (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This research aims to determine the effectiveness of the ice breaking method on the motivation to learn grammar among first-year female students at the Intermediate School of Muhammadiyah Teacher Training Institute, Bangkinang Kota, Kampar District. The research questions are: "Is the ice breaking method effective in motivating first-year students to learn grammar at the Intermediate School of Muhammadiyah Teacher Training Institute, Bangkinang Kota, Kampar District?" and "Which type of motivation increases the most after applying the ice breaking method?" The results indicate that the ice breaking method is effective in increasing grammar learning motivation among first-year students at the school. This is shown by the value of to being greater than tt. The result, to = 3.436, is greater than tt at a significance level of 5% = 2.013, meaning the alternative hypothesis is accepted and the null hypothesis is rejected. In conclusion, the type of motivation that increases the most after applying the ice breaking method is extrinsic motivation.